2006
DOI: 10.1152/ajpregu.00684.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary NaCl supplementation prevents muscle necrosis in a mouse model of Duchenne muscular dystrophy

Abstract: The mdx mouse is an animal model for Duchenne muscular dystrophy. Mdx mice fed a 12% NaCl diet from birth up to 20 days of age (mdx-Na mice) had an approximately 50% reduction in serum creatine kinase (CK) activity compared with mdx mice fed a standard diet. Most notably, necrotic fibers in tibialis anterior (TA) muscle of mdx-Na mice were reduced by 99% and were similar in control mice. These mdx mice displayed significantly elevated blood Ca2+ and Na+ levels, while the total calcium content of their TA muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 43 publications
3
26
0
7
Order By: Relevance
“…Considering that the R163C RyR1 mutation in skeletal muscle resulted in a significantly increased cytosolic Ca 2ϩ (about 2-fold of the normal resting concentration, this study and that by Yang et al (30), an activation of several calcium-dependent pathways was expected leading to the activation of a slow-twitch fiber program to increase the resistance to fatigue, the oxidative capacity, and the calcium buffering capacity of mitochondria. The values for total calcium contents of WT mitochondria evaluated in this study were within the range of those previously reported for rodent skeletal muscle using ICP-MS or other techniques (82)(83)(84)(85)(86). The significantly higher concentrations of mitochondrial calcium content in R163C reported here may stem from the chronically elevated (2-4-fold) resting intracellular Ca 2ϩ concentrations in intact MHS skeletal muscle from various species (76 -78).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Considering that the R163C RyR1 mutation in skeletal muscle resulted in a significantly increased cytosolic Ca 2ϩ (about 2-fold of the normal resting concentration, this study and that by Yang et al (30), an activation of several calcium-dependent pathways was expected leading to the activation of a slow-twitch fiber program to increase the resistance to fatigue, the oxidative capacity, and the calcium buffering capacity of mitochondria. The values for total calcium contents of WT mitochondria evaluated in this study were within the range of those previously reported for rodent skeletal muscle using ICP-MS or other techniques (82)(83)(84)(85)(86). The significantly higher concentrations of mitochondrial calcium content in R163C reported here may stem from the chronically elevated (2-4-fold) resting intracellular Ca 2ϩ concentrations in intact MHS skeletal muscle from various species (76 -78).…”
Section: Discussionsupporting
confidence: 84%
“…Given that exposure of mitochondria to a sustained higher calcium concentration may lead to higher calcium uptake and net calcium accumulation, dissipation of the electrochemical gradient, decreased ATP production, and/or organelle swelling or bursting (79 -81), the calcium concentrations in mitochondrial and PM fractions were evaluated in WT and R163C skeletal muscle by ICP-MS. The values for total calcium contents of WT were within those reported for rodent skeletal muscle using ICP-MS or other techniques (690 -1500 nmol/g muscle wet weight) (82)(83)(84)(85)(86). Skeletal muscle mitochondria from R163C mice had 5.7 times more Ca 2ϩ than WT, and the Ca 2ϩ concentration in the cytosolic fraction was 1.8-fold higher than WT (Table 4).…”
Section: Higher Mitochondrial Calcium In Ryr1 R163c Skeletal Muscle Isupporting
confidence: 73%
“…Muscles (DIA, STN, TA, and BB) were excised, and the animals were euthanized with an overdose of the anesthetic mixture. The muscles were weighed and digested with 0.2 ml ultrapure HNO 3 at 100°C as previously described (25,45). The samples were diluted to a final volume of 10 ml with ultrapure water.…”
Section: Methodsmentioning
confidence: 99%
“…Different treatment protocols, age groups, and endpoints have been used to assess the efficacy of drugs in mdx mice 24,6,8,9,11,14–16,20,21,31,33,37,39,42,45 (Table 1). Both trial design and endpoints should also consider data most attractive to the U.S. Food and Drug Administration in moving toward investigational new drug applications for initial human trials.…”
mentioning
confidence: 99%